PENGUATAN PEMAHAMAN WORK-LIFE BALANCE BAGI BIDAN DI KABUPATEN LOMBOK TENGAH - Novita Ana Anggraini; I Gusti Ayu Juliantari; Baiq Reni Pratiwi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Work–life balance is an important factor in maintaining the psychological well-being and work performance of healthcare workers, particularly midwives who face high work demands and multiple roles. This community service activity aimed to improve midwives’ understanding of the concept, impacts, and management strategies of work–life balance in Central Lombok Regency. The activity was conducted through an educational and participatory counseling program using the Satuan Acara Penyuluhan (SAP) method and involved 35 midwives. Evaluation was carried out using pre-test and post-test to measure changes in participants’ levels of understanding. The results showed a significant improvement in understanding, from 37.1% before the activity to 85.7% after the activity. Most participants were able to identify practical strategies for managing work–life balance and expressed readiness to apply them in their professional and personal lives. This activity was effective in increasing midwives’ understanding and awareness of the importance of work–life balance as a preventive effort against work-related stress and burnout and in supporting the improvement of healthcare service quality.